2012
DOI: 10.1007/s10682-011-9550-2
|View full text |Cite
|
Sign up to set email alerts
|

Divide and conquer: when and how should competitors share?

Abstract: When two individuals are unwilling to fight over a valuable resource, then they may obtain it with equal probability, or they may choose to divide the resource in some way. Although both strategies have been observed in nature, modelers have so far implicitly assumed that their long-term payoffs are the same. First we show that increasing returns to size in the value of a resource favor random allocation over sharing, whereas diminishing returns favor the reverse. Next we extend our approach to understand the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Food sharing has been observed in different animal species [ 62 65 ]. Even when both contenders play the same strategy, there usually are asymmetries increasing the probability that one of the contenders will keep all or most of the resource, but sharing remains a likely ESS in such circumstances and the stronger opponent should be less willing to divide the contested resource [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Food sharing has been observed in different animal species [ 62 65 ]. Even when both contenders play the same strategy, there usually are asymmetries increasing the probability that one of the contenders will keep all or most of the resource, but sharing remains a likely ESS in such circumstances and the stronger opponent should be less willing to divide the contested resource [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, an alternative endpoint to a dispute is to share the contested resource (Chamorro‐Florescano et al ., ; Eswaran & Neary, ). Mesterton‐Gibbons & Sherratt () recently extended the Hawk–Dove model to understand when and how sharing should evolve, and although they considered potential differences in RHP, they did not consider the effects of the more fundamental role asymmetry of owner and intruder. As physical sharing is an intuitively reasonable solution to conflict resolution that is occasionally observed, and as theory has already demonstrated that a nonfighting convention can maintain partitioning of space in the presence of a landmark (Mesterton‐Gibbons & Adams, ), it would be of interest to elucidate the effect of role asymmetry on physical sharing.…”
Section: Discussionmentioning
confidence: 99%